2021
DOI: 10.1038/s41467-021-24221-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cavity on interatomic Coulombic decay

Abstract: The interatomic Coulombic decay (ICD) is an efficient electronic decay process of systems embedded in environment. In ICD, the excess energy of an excited atom A is efficiently utilized to ionize a neighboring atom B. In quantum light, an ensemble of atoms A form polaritonic states which can undergo ICD with B. Here we investigate the impact of quantum light on ICD and show that this process is strongly altered compared to classical ICD. The ICD rate depends sensitively on the atomic distribution and orientati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…At present, the 2D mechanism of defect production, which is called interatomic Coulombic decay (ICD), is considered the prevalent mechanism of X-ray scattering in graphene [ 30 , 31 ] because the ICD is an efficient source of slow electrons. The ICD has been proposed as the prevalent mechanism of X-ray momentum relaxing in dimer molecules [ 32 ]. One of the two parts of the dimer is excited as a result of a Compton interaction with a projectile particle (photoionization), and then a photoelectron forms a repulsively bound pair with the other electron residing on the nearest lattice site (interatomic Coulombic electron capture) due to the Hubbard gap [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the 2D mechanism of defect production, which is called interatomic Coulombic decay (ICD), is considered the prevalent mechanism of X-ray scattering in graphene [ 30 , 31 ] because the ICD is an efficient source of slow electrons. The ICD has been proposed as the prevalent mechanism of X-ray momentum relaxing in dimer molecules [ 32 ]. One of the two parts of the dimer is excited as a result of a Compton interaction with a projectile particle (photoionization), and then a photoelectron forms a repulsively bound pair with the other electron residing on the nearest lattice site (interatomic Coulombic electron capture) due to the Hubbard gap [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to [ 38 ], the ICD of 2D materials both with and without band gaps proceeds in the same way. Taking into account the above and the fact that ultrafast ICD proceeds at times comparable to the time scale of electronic motion (see [ 32 ] and references therein), the ICD theory is not applicable to the interaction of -rays, swift heavy ions, and slow highly charged ions with graphene.…”
Section: Introductionmentioning
confidence: 99%
“…1,29−34 In a two-level model per molecule, it was shown that ϵ cav can increase with the number of molecules in a cavity (ϵ cav is proportional to the square root of this number, which can be in the order of 10 6 to 10 10 ). 35,36 See the proof for two-level-system approximation in the review of Nitzan and coauthors 1 and its use in most recent studies published in Nature Communications 12 and Physical Review Letters. 13 Therefore, let us start with the discussion of the TLS approach for a single molecule in a single cavity with a single photon.…”
Section: Introductionmentioning
confidence: 99%
“…by "exact diagonalization") have always been important test grounds for models and approximations. Recently, there is an intense interest in strongly coupled light-matter systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . In these systems, the lightmatter coupling cannot be treated perturbatively.…”
Section: Introductionmentioning
confidence: 99%